Investigating the factors influence adoption of internet banking in Malaysia: adopters perspective - Hong, Yong Hoe; Teh, Boon Heng; Vinayan, Gowrie; Chin, Hooi Soh; Nasreen Khan; Ong, Tze San (Canadian Center of Science and Education, 2013)
The main purpose of this research is to investigate the factors that influence adopters to take up the Internet banking services in Malaysia. The sampling units in this survey are the adopters of Internet banking who were using it for at least six months. A total of 116 useable questionnaires was coded and analyzed by using SPSS software. Statistical methods like descriptive analysis, factor analysis and regression analysis were used in this research. The regression results showed that Complexity, Security and Ccustomer Experience were the influencing factors of Internet banking services. However, Individual Characteristics was found to be partially influencing the adopters in their decision to adopt the Internet banking facilities.